A Missense Mutation rs781536408 (c.2395G>A) of TYK2 Affects Splicing and Causes Skipping of Exon18 in vivo - Chen, Suqing; Wu, Peilin; Wu, Bin; Lin, Chenye; Chen, Junhong; Chen, Lishengdan; Lv, Ge (Frontiers in Genetics, 2021)
TYK2 variants can impact disease onset or progression. In our previous study, we identified abnormal splicing happened near rs781536408 in TYK2 gene. This study aimed to explore the effect of the mutation on alternative splicing in vivo and in vitro. Whole exome sequencing (WES) was performed to identify the mutations followed by bidirectional Sanger sequencing. Then the mini-gene analysis was carried out based on HeLa and HEK293T cell lines. The results showed that rs781536408 (c.2395G>A, p.G799R) was homozygous in the patient, but heterozygous in parents. PCR amplification confirmed the abnormal splicing in the somatic cells of the patients, but not in the parents. Sanger sequencing results showed that there was a skipping of exon18 near the mutation. For mini-gene analysis, there was no difference between the wild type and the mutant type in the two minigene construction strategy, indicating that mutation c.2395G>A had no effect on splicing in vitro. Combining with the results of in vivo, we speculated that the effect of the mutation on splicing was not absolute, but rather in degree.